Do clinical trials affect anxiety, depression, and quality of life in the caregivers of patients with cancer? - Guo, Xiaotong; Lin, Lede; Qiu, Xiaohua; Tian, Meng; Zhu, Jiang (Frontiers in Psychiatry, 2022)
Objective: To investigate the effect of clinical trials on anxiety, depression and quality of life in the family caregivers (FCs) of cancer patients. Methods: FCs of patients participating in or not in clinical trials (group FCs-GCP (FG) and group FCs-nonGCP (FNG)) in the Cancer Center of West China Hospital were screened. We assessed FCs’ anxiety, depression and quality of life using Hospital Anxiety and Depression Scale and SF-12. The demographic characteristics of FCs and patients were analyzed. Results: The prevalences of anxiety and depression showed no significant difference between FG and FNG (46.3% vs 51.5%, P=0.604; 36.6% vs 51.5%, P=0.131, respectively). Physical Component Scores (PCS) were 48.87±7.67 for FG and 48.01±8.12 for FNG (P=0.618) while Mental Component Scores (MCS) were 48.92±7.78 and 44.89±11.42, respectively (P=0.031). FCs’ anxiety was positively associated with patients’ advanced disease (HR 4.292 [1.409, 13.072], P =0.010) and initial treatment (HR 3.105 [1.014, 9.515], P =0.047). Depression was positively related to advanced disease (HR 3.347 [1.140, 9.832], P =0.028) while negatively related to patients participating in clinical trials (HR 0.421 [0.180, 0.985], P =0.046) and FCs’ education degree (HR 0.355 [0.149, 0.843], P =0.019). MCS was positively associated with patients participating in clinical trials (β=5.067, 95%CI [0.817, 9.317], P =0.020) while negatively associated with advanced disease (β=-8.055, 95%CI [-19.804, 6.528], P =0.002). Conclusion: FCs of the cancer patients who participated in clinical trials showed a comparable worrying situation of anxiety and depression with the FCs of the regular cancer patients. More concern should be given to such a population, and the further study on them is warranted.